Empowering inclusive education: a multi-modal android application for accessible transliteration of Indian languages into Braille script. - Parida, Monnie; Bhattacharjee, Souvik; Dasgupta, Tirthankar; Sinha, Manjira; Basu, Anupam (Disability & Rehabilitation: Assistive Technology, 2025)
Objective: The primary objective of this application is to promote inclusivity in the educational environment by supporting special educators and students with visual disability in accessing, disseminating, and delivering educational resources that are accessible to all learners. This application specifically assists individuals with visual disabilities by transliterating Indian languages such as Bengali, Odia, Hindi, English, and Telugu into braille scripts, thereby enhancing access to educational content in native languages. Methods: The Android application was developed using Android Studio, with Java as the primary programming language and XML for designing the user interface. Audio functionality is supported through Automatic Speech Recognition (ASR), enabling voice-based interactions. The application offers a variety of input and interaction modes, including text input, audio based navigation, multilingual voice commands, gesture based controls, and compatibility with braille embossers. This design supports a multimodal, interactive accessibility framework that integrates input, processing, and output components. To evaluate the application's usability and accessibility, an initial round of unit testing was conducted, followed by feedback from special educators, students with visual disabilities, and researchers. Their insights were instrumental in validating the application's effectiveness and its relevance in the field of assistive technology. Impact: The android application serves as an affordable tool for individuals with visual disabilities, enabling access to educational materials in native languages and supporting braille learning. It empowers users to independently engage with educational content, thereby enhancing information access and promoting literacy and educational inclusion. IMPLICATIONS FOR REHABILITATION: Android application for transliterating Indian languages into Braille serves as an affordable tool for individuals with visual disabilities in accessing online educational materials in native languages and facilitating Braille learning. It enables seamless transliteration from Indian languages to its respective Braille script, empowering individuals with visual disabilities to independently engage with online content, thereby promoting literacy and educational inclusion. It features text-based input, voice navigation, multilingual voice input and Braille embossing compatibility, fostering independence, enhancing information access and facilitating educational and vocational pursuits for individuals with visual disability.